Panel VAR for Analyzing Business Cycle Influence on the Distribution of Sharia Banking Financing in Indonesian Sharia Banking - Mahjus Ekananda; Jhanghiz Syahrivar (Media Ekonomi dan Manajemen, 2023)
This paper is structured to explain the effect of the business cycle on the distribution of Islamic banking financing in Indonesia. Furthermore, this research examined the differences between account receivables financing and profit-sharing financing, as well as different forms of Islamic banking. In this case, Islamic banking financing, account receivables financing, and profit-sharing financing will have the same responses or changes in the face of the business cycle in Indonesia. This research is focused and limited to the response of Islamic banking financing to the business cycle in Indonesia. Second, this research used quarterly data from 2007 to 2020 obtained from financial data of each sharia commercial bank and sharia business unit published through the Financial Services Authority (OJK) and Bank of Indonesia; meanwhile, the macro-level data was taken from data from the Central Agency publication Indonesian Statistics. Third, the estimation method used is the Panel VAR to accommodate the heterogeneity between firms. The results show that capital and liquidity respond positively to changes in banking financing, account receivables financing, and profit-sharing financing. The results also show that performing loans and profitability will decrease if there is a shock to the three types of financing.